Anthraquinones from Hedyotis pinifolia - Duy, Le Hoang; Phi Phung, Nguyen Kim (Vietnam Journal of Chemistry, 2014)
Hedyotis pinifolia Wall ex G.Don (Vietnamsese name An điền lá thông), family of Rubiaceae, has not yet been chemically studied. From the aerial parts of H. pinifolia, four anthraquinones had been isolated: 1,6-dihydroxy-7-methoxy-2-methylanthraquinone (1), 1,6-dihydroxy-2-methylanthraquinone (2), 3,6-dihydroxy-2-methylanthraquinon (3) and 1,3,6-trihydroxy-2-methylanthraquinone (4). Their chemical structures were established by spectroscopic analysis.